Factors affecting the diagnostic performance of circumpapillary retinal nerve fibre layer measurement in glaucoma - Wong, Damon Wing Kee (2021)
Background/aims: To identify factors that influence the diagnostic performance of circumpapillary retinal nerve fibre layer (RNFL) thickness measurements in the detection of primary open-angle glaucoma (POAG). Methods: 1592 eyes from 1076 healthy controls and 758 eyes from 502 patients with POAG underwent optical coherence tomography (OCT) imaging to assess RNFL parameters. Visual field (VF) mean deviation (MD) from standard automated perimetry was used to indicate severity in subjects with glaucoma. Results: RNFL thickness significantly decreased with age (ρ=−0.10 to −0.16, p<0.001) and increased with spherical equivalent (SE) refractive error (ρ=0.23–0.29, p<0.001) in healthy and glaucoma groups but showed a significant reduction with SE (ρ=−0.20, p<0.001) in the temporal RNFL of healthy subjects. RNFL measurements significantly decreased with VF MD (ρ=0.08–0.53, p<0.05) in subjects with POAG. When healthy subjects and subjects with glaucoma were matched to subgroups within a factor, significant differences in area under the curve (AUC) between subgroups were only found with SE AUCs increased significantly with disease severity, particularly in the global, inferior and superior measurements (p<0.001). Overall, the diagnostic performance of the inferior and global RNFL measurements were found to be more resilient to different factors.Conclusion: Diagnostic accuracy in glaucoma was influenced by SE but could be mitigated by using controls with similar refractive characteristics. Increasing disease severity led to significantly better diagnostic accuracy. These factors should be considered when using OCT for glaucoma diagnosis in practice.